Cancer Epidemiology and Program Implementation in Low and Middle Income (LMI) Countries: A Lesson to Learn - -, A Lesson; Thomas, David B (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478425/Cancer-Epidemiology-and-Program-Implementation-in-Low-and-Middle-Income-LMI-Countries-A-Lesson-to-Learn